PEDAGOGICAL CHALLENGES IN TEACHING FOLKLORE TO CHILDREN IN NON-FORMAL EDUCATION: A CASE STUDY FROM BULGARIA: PEDAGOGICAL CHALLENGES IN TEACHING FOLKLORE TO CHILDREN IN NON-FORMAL EDUCATION: A CASE STUDY FROM BULGARIA - Budakova, Stefka (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
This study analyzes data from a survey conducted among non-formal education teachers engaged in teaching folklore to children. It investigates effective practices and challenges these educators encounter in the transmission of folklore traditions to contemporary youth. Drawing on the collected data, the research proposes targeted strategies to enhance and optimize the teaching process, addressing the specific needs of both students and educators within this cultural and pedagogical context.